Analisis Green Accounting Antara Kepedulian Dan Pemahaman Pelaku UMKM - Jejen Jaenudin; Nastiti Rizky Shiyammurti; R. Enough Bhaktiar; Hari Satia Nugraha; Sri Mulyeni (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study examines the understanding and concern of MSMEs towards Green Accounting. This study uses a qualitative descriptive method with data collection through interviews, observations and documentation. The informants in this study were business actors in Cimahi Tengah District, Cimahi City. The results of the study indicate that business actors' understanding situs slot gacor777 of Green Accounting is still lacking, as evidenced by the absence of records in the financial reports made regarding the budget or cost analysis of Green Accounting. The lack of knowledge of business actors is due to the lack of information received from both the government and other institutions. However, business actors already have an awareness of protecting the environment by sorting organic and non-organic waste by separating them in different places. Business actors record the cost of cleaning up waste as additional costs or variable costs, in addition to other forms of awareness that business actors already have by providing social assistance to the community around the place of business where this is part of the concern for the environment that has been carried out by business actors.